Safety aspect in installation industrialized building system (IBS) component - Noor Yuhana, Maamor (2009)
Safety aspect in construction is very importance and it has to apply to any construction project. It can be lead to accidence that could cause injured to workers as well the public and some causes can lead to death. Pre-cast construction also not exclude from having hazard in its construction process during the installation component. However, the most construction accidents occur because lack of proper planning, unsafe equipment, not follow the method statement, unsafe site conditions, not using the safety equipment that was provided, and poor attitude towards safety during installation process. The aim of this project is to study the process of installation component pre-cast concrete and to identify the safety aspect and the requirement during the process installation at site, included to identify the level of safety during installation process at site. The data was collected through documents study, interview, and industrial visit, constructed and distributed questionnaire in order to identify the safety requirements in pre-cast construction. All of the interview and research questionnaire survey are conducted among contractor that registered as class 7 with Construction Industrial Development Board (CIDB) and class A with Pusat Khidmat Kontraktor (PKK) in Klang Valley. Returned questionnaire were analyses with used average index and frequency analysis method to identify safety aspect using pre-cast construction. The results indicate that the safety aspect implemented by company involved in precast construction process is at a good level at safety aspect during bracing, propping, welding and grouting process and very good level at safety in general aspect and safety aspect during lifting process. This are a few safety aspect and requirement during installation process such as construction site workers equipped with personal protective equipment (PPE) and etc. In conclusion with existence of this study, it can boost up knowledge and give detailed information about safety aspect in Industrialized Building System using pre-cast concrete and must improve step of awareness until 0% of accident.